Pemanfaatan dan Pengembangan Sumber Daya Manusia Berbasis Gender: Partisipasi Wanita TNI dalam Misi Perdamaian Global - Relycia Solihin; Anisa Ardhian; Widya Anggoro (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2025)
Since the adoption of UN Security Council Resolution 1325 on Women, Peace, and Security, women’s participation in peacekeeping missions has become a strategic issue. In Indonesia, female military personnel represent only 5% to 10% of the force, which is far below the UN target of 15% by 2028. This gap reflects the difference between policy commitments and practical realities, as women’s roles often remain symbolic rather than strategic. This study analyzes the participation of female personnel of the Indonesian National Armed Forces (TNI) in the UNAMID mission and examines the strategies of the Ministry of Defense, Ministry of Foreign Affairs, TNI Headquarters, and the TNI Peacekeeping Mission Center. It identifies supporting and limiting factors and evaluates their relevance to Indonesia’s defense diplomacy and the Sustainable Development Goals (SDGs).Using qualitative methods, the study involves interviews and document analysis, with triangulation to ensure validity. Findings show that female TNI personnel contribute significantly in health services, psychosocial support, and community engagement. Their participation goes beyond quotas and represents a strategic factor in the effectiveness of peace operations and Indonesia’s defense diplomacy. Academically, this research enriches the study of international relations and defense by incorporating gender perspectives as a critical dimension of global security. It highlights the need to internalize gender equality values within military culture through education, public awareness, and policy advocacy, while expanding gender-based peace diplomacy in international forums to enhance global legitimacy.